If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -5(12x + 8) = 0 Reorder the terms: 8 + -5(8 + 12x) = 0 8 + (8 * -5 + 12x * -5) = 0 8 + (-40 + -60x) = 0 Combine like terms: 8 + -40 = -32 -32 + -60x = 0 Solving -32 + -60x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -60x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -60x = 0 + 32 -60x = 0 + 32 Combine like terms: 0 + 32 = 32 -60x = 32 Divide each side by '-60'. x = -0.5333333333 Simplifying x = -0.5333333333
| 3x=6-2y | | 2c+2+5c= | | 6x=70 | | 4x^4-4x^2+1=0 | | xy+(y)(y)=-5 | | m/5+4=18 | | x-2y=-3 | | 12-60=3-k | | 19x+3y=23 | | 27.48=p-28 | | 5(5t-2)=35 | | 5. 19=-3a-5 | | 3x^4-4x^2+1=0 | | 2(x^3+2x^2+3x+12)=0 | | 48*12= | | p(x)=x^4-8x^3-4x^2+33x-8 | | 3x+5=60 | | 4x+2y=3 | | 7y+8=15y-(16+24) | | j-5=-5 | | 14(n+7)=(n-4) | | -21-15m=219 | | 4=h+5 | | 5y-3y+3+6= | | 5x-7-2x=2 | | 15+2(x-10)=3(2x+1)-18 | | 6x+4=8x-5 | | w-4=1 | | 3xy=6 | | w=12-w | | 19=-3a-5 | | y^2-14y-13=7 |